PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DI CATATAN SIPIL KABUPATEN BIMA - Rena Tri Febrianti; Yusuf, Muhammad; Badar, Muh (Publika Citra Media, 2024)
This research aims to determine the influence of organizational culture and work environment on employee job satisfaction at the Bima Regency Population and Civil Registration Service. The approach used in the research is an associative approach. The population in the study was 121 people with a sample of 35 ASN people. The data collection techniques used were observation, questionnaires and literature study. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, T test and F test which were processed using the Statistical Product and Service Solution (SPSS) version 20 program. that Organizational Culture (X1) and Work Environment (X2) simultaneously have a significant effect on Employee Job Satisfaction at the Bima Regency Population and Civil Registration Service.